Knowledge of Drugs that Require Liver-Based Dosage Adjustments - A Survey Based Study - Dr. Krithika Sri,; Barath Raj.R,; Syed Sumyaa Shirin,; Nivas S,; Kalaikumar K,; Vangara Anirudh,; Aashikha A, (International Journal of Scientific Research in Science and Technology, 2025)
Background: Liver dysfunction significantly alters drug metabolism, increasing the risk of toxicity or therapeutic failure if doses are not properly adjusted. Despite its clinical relevance, healthcare professionals may lack adequate knowledge about hepatic dose modifications. Objective: To evaluate the awareness and understanding of healthcare professionals and healthcare students regarding drug dose adjustments required in liver impairment. Methodology: A cross-sectional, questionnaire-based survey was conducted among 40 participants, including students and practicing professionals in the medical and pharmacy fields. The survey assessed knowledge of hepatic drug metabolism, identification of high-risk drugs, and familiarity with tools like the Child-Pugh classification used for clinical decision-making. Results: Findings revealed moderate knowledge gaps among respondents. While most were aware that liver function affects drug dosing, many failed to identify commonly used drugs that require adjustment, such as warfarin, paracetamol, and benzodiazepines. Only a small portion of participants reported understanding or use of the Child-Pugh scoring system. These findings are consistent with previous research highlighting limited awareness and inconsistent practices among healthcare providers. Conclusion: The study demonstrates a need for improved education and training on hepatic dose adjustment. Integrating this content into undergraduate curricula and ongoing professional development may help reduce prescribing errors and enhance patient safety in those with liver impairment.
Keywords: Liver dysfunction; Dose adjustment; Drug metabolism; Child-Pugh classification; Healthcare awareness